2009
DOI: 10.1248/bpb.32.517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on S-Warfarin and Diclofenac Metabolism by Recombinant Human CYP2C9.1

Abstract: Warfarin, which consists of a racemic mixture of S-and Renantiomer, has been used as an anticoagulant agent. The anticoagulant activity of S-warfarin is 3-5 times greater than that of R-warfarin.1) This drug has a narrow therapeutic index and shows marked drug-drug interactions when coadministered with other agents that alter warfarin metabolism.2,3) The stereoselective metabolism of warfarin enantiomers in humans has been shown to be catalyzed by cytochrome P450 (CYP) such as CYP1A1/2, 2C9, and 3A4. 4,5) The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
(10 reference statements)
2
8
1
1
Order By: Relevance
“…In our population, acenocoumarol final weekly maintenance dose was affected by age, target INR range, and alcohol intake. All research participants who reported alcohol use were occasional drinkers, and none had evidence of liver disease; note that it has been previously shown that ethanol may inhibit drug metabolism by CYP2C9 41 , 42 . The use of the CYP2C9 inhibitor amiodarone did not play a major role; it is possible that this is due to the low number of patients taking this drug.…”
Section: Discussionmentioning
confidence: 89%
“…In our population, acenocoumarol final weekly maintenance dose was affected by age, target INR range, and alcohol intake. All research participants who reported alcohol use were occasional drinkers, and none had evidence of liver disease; note that it has been previously shown that ethanol may inhibit drug metabolism by CYP2C9 41 , 42 . The use of the CYP2C9 inhibitor amiodarone did not play a major role; it is possible that this is due to the low number of patients taking this drug.…”
Section: Discussionmentioning
confidence: 89%
“…However, the inhibitory effect of ethanol on the 4'-hydroxylation of diclofenac was not observed even at 1.0 vol% (170 mM) ethanol. Ethanol at a concentration of 3.0 vol% (510 mM) increased the K m value of diclofenac metabolism without changes in the V max , which indicates that diclofenac 4'-hydroxylation by CYP2C9 was competitively inhibited by ethanol [1367]. These results indicate that S-warfarin metabolism by CYP2C9 is more sensitive to ethanol than diclofenac metabolism and ethanol inhibits the metabolism by CYP2C9 in a substratedependent manner.…”
Section: Ethanolmentioning
confidence: 81%
“…In recombinant CYP2C9, the 7-hydroxylation of S-warfarin was inhibited by as low as 0.1 vol% (17 mM) ethanol [1367]. Ethanol decreased the V max /K m and V max values of S-warfarin metabolism in a concentration-dependent manner, but the K m value was unchanged by ethanol.…”
Section: Ethanolmentioning
confidence: 94%
“…In fact, the influence of ethanol on CYP2C9 activity seems to be substrate dependent, with a significant inhibition on warfarin metabolism at 0.1 vol% and no inhibition of diclofenac metabolism at 1 vol% (Tatsumi et al. ). In general, the influence of ethanol on CYP2C9 differs from that on CYP2D6, where Hellum and Nilsen () found a biphasic effect with a small inhibition at 0.1%, a significant activation at 0.5%, 0.8%, 1.1%, 1.5%, and 5%, and a significant inhibition at 8% and 15%.…”
Section: Discussionmentioning
confidence: 99%